Strategi Hubungan Masyarakat dalam Meningkatkan Citra SMK Hidayah Kota Semarang - Nadia Anggraeni , Nadia Anggraeni; Pramusinto, Hengky (Universitas Negeri Semarang, 2024)
This study aims to investigate public relations strategies, obstacles faced, and steps taken by public relations to improve the image of prospective students SMK Hidayah Semarang City. This type of research uses qualitative descriptive analysis, data collection techniques for this research use observation, interviews and documentation methods. The research results show that the Public Relations strategy at SMK Hidayah Semarang consists of publications, events, news, community involvement, inform or image, lobbying, and negotiations, social responsibility; Obstacles that occur in carrying out the public relations strategy of SMK Hidayah Semarang, namely the lack of human resources to assist the performance of public relations in schools, and the existence of zoning system regulations; Efforts made by Public Relations to overcome obstacles are by involving all school staff to help with Public Relations activities, either collaborating with other Head of Student Affairs, or requiring teachers to create WhatsApp stories as a form of promotion, and put up banners, distribute brochures, and publicize via the SMK website guidance. This research provides information as a form of evaluation for public relations in schools regarding public relations marketing management